Implementasi Kegiatan Storytelling Based Cutting untuk Stimulasi Motorik Halus Anak Usia 3-4 Tahun - Kholipah, Siti; Pipit Rika Wijaya, Pipit Rika Wijaya; Rizki Sevi Triana , Rizki Sevi Triana (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2025)
Fine motor skills are a crucial aspect of early childhood development, particularly as a foundation for preparing pre-writing abilities. One relevant form of stimulation is cutting activities. However, children's interest in this activity tends to be low due to monotonous and less varied teaching methods. This study aims to improve the fine motor skills of children aged 3–4 years through storytelling-based cutting activities. The study adopted a Classroom Action Research (CAR) approach following the spiral model proposed by Kemmis and McTaggart, conducted in two cycles. The research subjects were students of the Dewi Masyithoh II playgroup. Data were collected through observation and documentation techniques. The findings of this study indicate that cutting straight-line patterns on animal-themed paper combined with a storytelling approach could enhance children's learning motivation and fine motor skills. In addition, individualized guidance proved effective in assisting children who experienced difficulties in cutting. The percentage of children categorized as developing as expected or very well increased from 9.09% in the initial condition to 54.54% during the first cycle, and reached 81.81% during the second cycle. Thus, the storytelling-based cutting approach is proven effective in supporting the development of fine motor skills in early childhood